The role of cytokine genetic polymorphism in development of acute pancreatitis: analysis of intergenic and environmental interactions - T. A. Samgina; G. A. Zhivotova; P. M. Nazarenko; A. V. Polonikov (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim of investigation. To study association interleukin-1 (IL-1) gene (rs16944), interleukin-6 (IL-6) gene (rs1800795), interleukin-10 (IL-10) gene (rs1800896) polymorphisms with development of acute pancreatitis (AP) in the Russian population. Material and methods. Whole blood samples were received from 297 AP patients and 238 healthy controls. Genotyping of IL-1 gene (rs16944) polymorphisms, IL-6 gene (rs1800795), IL-10 gene (rs1800896) was carried out by polymerase chain reaction with allele discrimination by TaqMan-probes. Results. The genetic polymorphism combination 511СТ×174GC of IL-1 and IL-6 genes was associated to high risk of AP development (OR=2.25, 95%-CI 1.45-3.49; p=0.0018). According to stratification analysis smoking patients with 511CT genotype had higher AP risk, then the patients with other genotypes (OR=2.22, 95%-CI 1.3-3.79; p=0.003). Paired combination of genotypes to disease risk analysis demonstrated that at 511СT×174GС genotype combination the AP risk is highest at alcohol abuse history for over 10 years (OR=2.88, 95%-CI 1.59-5.23; p=0.0004). Conclusion. Interleukin genetic polymorphism investigation may be useful at assessment of cytokine status in AP patients to predict the outcomes and to develop the personalized approach to treatment and prophylaxis.